Three Cases of Boerhaave’s Syndrome Treated via Laparoscopic Transhiatal Esophageal Repair - Ryosuke Kita; Hiroyuki Kobayashi; Kai Nakao; Kentaro Iwaki; Masato Kondo; Satoshi Kaihara (Case Reports in Gastroenterology, 2022)
Spontaneous esophageal perforation in Boerhaave’s syndrome results in significant morbidity and mortality. The gold standard treatment for this disease is thoracotomy and laparotomy because it can be a life-saving procedure that can be performed in emergencies; however, minimally invasive surgery has recently been reported. This report describes three cases of Boerhaave’s syndrome that were treated using laparoscopic transhiatal suture and omental patch. One patient recovered uneventfully and was discharged from the hospital after 12 days. The other 2 patients had postoperative complications, such as minor leakage and remnant abscess (Clavien-Dindo Grade II), but were discharged from the hospital after 17 days and 30 days, respectively. In the case of Boerhaave’s syndrome with localized mediastinal collections, a good clinical course can be obtained by laparoscopic transhiatal esophageal repair to avoid surgical invasion due to thoracotomy.